Assessing Language Learners’ Knowledge and Performance during Covid-19 - Huszti, Ilona; Fábián, Márta; Lechner, Ilona; Bárány, Erzsébet (Central European Journal of Educational Research, 2021)
The new reality created by the COVID-19 caused a lot of changes in the educational sphere. The transition from face-to-face to distance learning was not smooth in Ukraine because distance learning was not a common practice in the country before and teachers were unprepared for teaching online. This unusual situation prompted us to start our qualitative research primarily to get insights into the altered daily routines of teachers and educators. In particular, we were interested in how they assessed their students’ performance online. This article focuses on secondary school language teachers (n=65) and language tutors at the tertiary level (n=18). The research findings have revealed that teachers gave feedback through different digital applications like Google Classroom. Oral performance was evaluated either synchronously or asynchronously. The most crucial implication is that teachers should improve and further develop their digital skills and distance teaching and assessing skills in order to provide quality education in the modern form.